Effective Piezo-Phototronic Enhancement of Flexible Photodetectors Based on 2D Hybrid Perovskite Ferroelectric Single-Crystalline Thin-Films - Ding, Ran (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2021 Wiley-VCH GmbH.